Analisa Kompetensi Soft Skill Mahasiswa Praktek Pengelolaan Zakat (Ppz) Febi IAIN Kediri (Studi Persepsi Pengurus Lazisnu Kediri) - Mauludin, M Soleh; Soimah, Zakiyatus (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
This research aims to analyze the soft skills competencies of students in the Sharia Banking Study Program, Faculty of Islamic Economics and Business (PPZ FEBI) of the State Islamic Institute (IAIN) Kediri based on the perceptions of the management of the Amil Zakat, Infaq and Shadaqah Nahdlatul Ulama Institute (LAZISNU) Kediri. Soft skill competencies are non-technical skills that are very important in the world of work, including communication skills, teamwork, leadership, time management, and problem-solving. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews with LAZISNU Kediri administrators who have experience working with PPZ FEBI IAIN Kediri students. The research results show that LAZISNU Kediri administrators generally assess PPZ FEBI IAIN Kediri students as having good soft skill competencies, especially in communication and teamwork. However, several aspects still need to be improved, such as time management and problem-solving abilities. It is hoped that these findings can provide input for study programs in developing curricula and extracurricular activities that are more effective in improving students' soft skill competencies.